Performance progression of elite jumpers: early performances do not predict later success - Boccia, G.; Cardinale, M.; Brustio, P. R. (Scandinavian Journal of Medicine & Science in Sports, 2021)
This study aimed 1) to estimate the transition rate for top 50 ranked track and field jumpers 2) to compare the performance progression of top 50 ranked senior jumpers (top50 senior) to those who failed to be top 50 ranked in the senior category despite being top 50 ranked in the under 18 category (only U18) and 3) to verify if relative age effect may at least partially explain the differences in the two above-mentioned subgroups.